2023
DOI: 10.3389/fphys.2022.998424
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation in premature ovarian failure: A literature review

Abstract: Premature ovarian failure (POF), or premature ovarian insufficiency (POI), is a multifactorial and heterogeneous disease characterized by amenorrhea, decreased estrogen levels and increased female gonadotropin levels. The incidence of POF is increasing annually, and POF has become one of the main causes of infertility in women of childbearing age. The etiology and pathogenesis of POF are complex and have not yet been clearly elucidated. In addition to genetic factors, an increasing number of studies have revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 180 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…Several studies have highlighted the significance of epigenetic modifications, such as changes in DNA methylation levels, histone modifications, and non-coding RNA expression, in the aging process of germ cells and early embryos [48,49]. Abnormal DNA methylation on critical gene promoters in granulosa cells and cumulus cells has been associated with adverse effects on ovarian function in older women [50].…”
Section: Hallmarks Of Aging and Ovarian Functionmentioning
confidence: 99%
“…Several studies have highlighted the significance of epigenetic modifications, such as changes in DNA methylation levels, histone modifications, and non-coding RNA expression, in the aging process of germ cells and early embryos [48,49]. Abnormal DNA methylation on critical gene promoters in granulosa cells and cumulus cells has been associated with adverse effects on ovarian function in older women [50].…”
Section: Hallmarks Of Aging and Ovarian Functionmentioning
confidence: 99%
“…Investigating the various pathophysiological mechanisms underlying female reproductive disorders may provide specific targets for effective infertility treatment and the prevention of long-term complications in this patient population. Recent studies have suggested that noncoding RNAs may play a role in regulating the pathophysiology of female reproductive disorders [10][11][12], offering a potential avenue for novel treatment strategies. Over the past decade, a growing body of evidence has shown that noncoding RNAs, recognized as pivotal post-transcriptional regulators in various diseases, can also govern the physiological processes of sex steroid biosynthesis and secretion [10,13].…”
Section: Introductionmentioning
confidence: 99%